Post-Harvest Technologies and Automation: Al-Driven Innovations in Food Processing and Supply Chains - Barnavo Das,; Azmirul Hoque,; Suranjit Roy,; Kundan Kumar,; Ahad Ahmed Laskar,; Ahmed Sadique Mazumder, (International Journal of Scientific Research in Science and Technology, 2025)
The rapid advancements in artificial intelligence (AI) and automation are transforming post-harvest technologies, offering innovative solutions to improve food quality, safety, and supply chain efficiency. This paper reviews the role of AI-driven innovations in post-harvest food processing and logistics, with a focus on automation, predictive analytics, and quality control. AI technologies, such as machine learning, computer vision, and IoT integration, are optimizing processes like sorting, grading, packaging, and microbial detection, reducing food waste and extending shelf life. Moreover, AI-powered robotics and smart warehouses are streamlining transportation and inventory management, enhancing operational efficiency. The integration of AI in demand forecasting and supply chain optimization is further improving food traceability, minimizing disruptions, and reducing environmental impact. Despite the promising potential, challenges such as data quality, system integration, cost barriers, and regulatory concerns remain. The future of AI in post-harvest technologies presents opportunities for continued innovation, with advancements in deep learning, IoT, and global scalability, offering pathways to sustainable food systems. This paper concludes by discussing the impact of AI on the post-harvest sector and its potential to drive more efficient, resilient, and sustainable food supply chains worldwide.
Keywords: Artificial intelligence (AI); Post-harvest technologies; Food processing; Supply chain optimization; Automation; Sustainability